Enhanced Expert Systems - Vizureanu, Petrică (IntechOpen, 2019)
The theoretical approach of this book is to develop a primary survey of the knowledge representation model, providing convergence of classical operations research and modern knowledge engineering. This convergence creates new opportunities for complicated problems of formalization and solution by integrating the best features of mathematical programming or constraint programming. This book explains in six chapters that expert systems are products in the field of computer science that attempt to perform as intelligent software. What is outstanding for expert systems is the applicability area and the solving of different problems in many fields or industrial branches.